Neugestaltung der Förderinstrumente für Arbeitslose: Zum Gesetzentwurf zur Verbesserung der Eingliederungschancen am Arbeitsmarkt - Lutz Bellmann; Stefan Bender; Stefan Bernhard; Andreas Crimmann; Hans Dietrich; Martin Dietz; Anette Haas; Andreas Hirseland; Barbara Hofmann; Katrin Hohmeyer; Susanne Koch; Marion König; et al. (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
Die Bundesregierung will mit ihrem Gesetzentwurf zur Verbesserung der Eingliederungschancen am Arbeitsmarkt (Bundestagsdrucksache 17/6277) die Integration in Arbeit oder Ausbildung beschleunigen und den Bereich der öffentlich geförderten Beschäftigung neu ordnen. Die Absicht der Bundesregierung, die Effektivität und Effizienz der Arbeitsmarktpolitik durch mehr Dezentralität, Flexibilität, Individualität, Qualität und Transparenz zu sichern, schlägt sich in einer Vielzahl von Einzelregelungen und einer Neuordnung des Instrumentenkastens nieder. Die Veränderungen betreffen sowohl Leistungen der aktiven Arbeitsförderung (Sozialgesetzbuch Drittes Buch) als auch Eingliederungsleistungen in der Grundsicherung für Arbeitsuchende (Sozialgesetzbuch Zweites Buch). In ihren Anträgen kritisieren die Fraktionen von SPD (Arbeitsmarktpolitik an den Herausforderungen der Zeit orientieren - Weichen für gute Arbeit, Vollbeschäftigung und Fachkräftesicherung stellen, Bundestagsdrucksache 17/6454), Bündnis 90/Die Grünen (Arbeitsmarktpolitik - In Beschäftigung und Perspektiven investieren statt Chancen kürzen, Bundestagsdrucksache 17/6319) und Die Linke (Arbeitsmarktpolitik neu ausrichten und nachhaltig finanzieren - Bundestagsdrucksache 17/5526) dagegen eine einseitige Konzentration auf den arbeitsmarktnahen Personenkreis und fordern eine stärkere Beachtung von Menschen mit verfestigten Vermittlungshemmnissen. Das IAB geht in seiner Stellungnahme auf die Intention des Gesetzesvorhabens ein und äußert sich aufgrund der vorliegenden Forschungsbefunde zu ausgewählten Aspekten des Gesetzentwurfs der Bundesregierung sowie der einzelnen Anträge der Oppositionsfraktionen. – – With its draft law on improving integration opportunities on the labour market (parliamentary printed document 17/6277), the Federal Government is intending to speed up the process of integration into work or training and reorganise the area of publicly subsidized employment. The intention of the Federal Government of securing the effectiveness and efficiency of labour market policies through a higher degree of decentralisation, flexibility, meeting individual needs, quality and transparency. This intention is reflected in a great variety of individual regulations and the reorganisation of the range of instruments available. The changes affect both active employment promotion (Book III of the Social Code) as well as specific instruments that aim at improving the labour market prospects of job-seekers receiving welfare benefit (Book II of the Social Code). In their motions, the parliamentary groups of the Social Democratic Party, SPD (Orientating labour market policy on the current challenges - Setting the course for gainful work, full employment and maintaining a sufficient supply of skilled workers, parliamentary printed document 17/6454), Alliance 90/The Greens (Labour market policy - Investing in employment and perspectives instead of diminishing opportunities, parliamentary printed document 17/6319) and The Left (Giving labour market policy a new direction and financing it sustainably, parliamentary printed document 17/5526) criticise that the reform is rather concerned with improving policies and prospects of persons that are relatively easy to place. They demand from the Federal Government to pay more attention to needs of people with considerable placement impediments. In its comment, IAB responds to the intention of the proposed legislation and offers its opinion on the basis of existing research findings on selected aspects of the draft law of the Federal Government as well as of the individual motions of the opposition parties.
Keywords: 330